PENGARUH GOOD CORPORATE GOVERNANCE TERHADAP KINERJA KEUANGAN BANK UMUM SYARIAH - Indriyani Indriyani; Rinda Asytuti (AKURASI: Jurnal Riset Akuntansi dan Keuangan, 2019)
This study aims to determine the effect of Good Corporate Governance on Islamic banking financial performance as measured by Return On Assets. The Good Corporate Governance used in this study is the board of commissioners, the board size, audit committee size, sharia supervisory board size, and Islamic social reporting. The population in this study is all Sharia Commercial Banks in Indonesia. The sample used was 9 Islamic commercial banks from 2015-2018. The data analysis technique used is multiple linear regression test. The results showed that the size of the board of commissioners and ISR partially had a significant negative effect on ROA. While the size of the board of directors, the size of the audit committee and the size of the sharia supervisory board have no significant effect on ROA.